Ilustração do livro infantil, uma multiplicidade de linguagens - Calado, Teresa Salinas, 1973- (2018)
One of the treasures of illustrating children’s books is the multiplicity of languages that can be discovered when exploring forms, colours, materials and techniques, while looking for the best way to communicate the messages that the book, page by page, intends to convey. This Communication shows the way followed during my doctoral project in Drawing area. Throughout this pathway I have tested several possibilities of visual composition, combining different styles of drawing, of representation techniques, supports and materials, which implied the use of resources such different as the sketch book and the computer. With this I intend to exemplify the work of the illustrator and the variety of plastic expressions which, depending on the path he chooses to follow, may result in different styles of illustration, created by only one author